Efficacy and Safety of Apatinib in Patients with Recurrent Glioblastoma - Hao Lin; Xinli Zhou; Xiaofang Sheng; Xiaohua Liang (Adis, Springer Healthcare, 2023)
Abstract Background and Objective Glioblastoma is a cranial malignant tumor with a high recurrence rate after surgery and a poor response to chemoradiotherapy. Bevacizumab has demonstrated efficacy in the treatment of glioblastoma by inhibiting vascular endothelial growth factor, but the efficacy of vascular endothelial growth factor receptor tyrosine kinase inhibitors varies in treating glioblastoma. This single-arm prospective study aimed to explore the efficacy and safety of the vascular endothelial growth factor receptor tyrosine kinase inhibitor apatinib in treating recurrent glioblastoma after chemoradiotherapy. Methods A total of 15 patients with recurrent glioblastoma (2016 World Health Organization grade IV) after chemoradiotherapy were enrolled in this study from September 2017 to September 2019 and treated with apatinib 500 mg once daily. Responses were evaluated according to the Response Assessment in Neuro-Oncology criteria, and adverse events were recorded according to the National Cancer Institute Common Terminology Criteria for Adverse Events Version 4.0. Results The overall response rate was 33.3%, and the disease control rate was 66.6%. The median progression-free survival was 2 months, and the median overall survival was 6.5 months. The apatinib dose was adjusted in seven patients because of adverse events (46.6%). The most common adverse events were thrombocytopenia (53.3%), asthenia (40%), and hand-foot syndrome (33.3%). Conclusions Apatinib might be effective in treating recurrent glioblastoma after chemoradiotherapy in terms of the overall response rate, but the efficacy is not durable and the clinical benefit is limited. The adverse effects of apatinib were acceptable. Clinical Trial Registration ChiCTR-ONC-17013098, date of registration: 24 October, 2017.